A study to assess effectiveness of information booklet on knowledge regarding intellectual disability and attitude towards disabled children among parents at Manovikas vishesh vidyalay, Aghanpur, Dharampura Jagdalpur, C.G - k Paul, Elby; MAJUMDAR, JYOTI MAJUMDAR (Innovative Journal of Medical and Health Sciences, 2024)
ABSTRACT Intellectual disability is defined as a condition of arrested or incomplete development of the mind, which is especially characterized by impairment of skills manifested during the development period, which contribute to the overall level of intelligence, i.e., cognitive, language, motor and social abilities. The disability originates before the age 18. There is general agreement that a person with intellectual disability must have significantly sub-average intellectual functioning. These children are mostly neglected by parents due to their disability and kept separated from society, because of lack of knowledge and negative attitude of parents. The investigator felt that this lack of knowledge of parents will affect the intellectually disabled children physical and mental health which will be caused by parent’s ignorance. This influenced the investigator to take up this study to assess the effectiveness of information booklet on knowledge and attitude on intellectual disability among parents of children with intellectual disability. The goal is to bring awareness among parents with proper knowledge about the disability, so that the children with disability will be properly taken cared. The findings of the study reveal that out of 50 parents, overall knowledge among parents the total mean score was 13.42 and standard deviation of 3.065 in pre-test. And in posttest the mean score is 22.08 with standard deviation 5.159. Overall attitude among parents, the total mean score was 36.4 with standard deviation 3.60 in pretest and in posttest overall attitude among parents of mean score 81.42 with standard deviation 4.23. Also, in pre-test the knowledge level is 80% average and 20% good knowledge found, and in posttest 44% average, 48% good and 8% excellent knowledge found after distribution of information booklet. Then in pre-test attitude level 94% parents have negative attitude, 6% have positive attitude and in posttest 90% of parents have positive attitude and 10% have negative attitude. The above result signifies that there has been a consistent increase in knowledge level in posttest as compared to pre-test and attitude level also changed from negative to positive. Analysis for association between the selected demographic variables with pre-test knowledge was using chi-square test and found significant association among parents and mother’s education, family monthly income, type of family and source of knowledge and rest of all association between knowledge and attitude with socio-demographic variable data is insignificant at the level of p<0.05. Based on the findings of the study, the major implication for nursing was that, this study does provide information to the parents to improve their knowledge and attitude on intellectual disability. The study concluded that the information booklet on intellectual disability was effective in increasing the knowledge of parents